Ways of learning in times of pandemic: Deficiencies and the importance of digital inclusion for public school students - Oliveira, Herbert Fernando Martins de (2021)
This article addresses the central contemporary issue: digital access to education. This is a bibliographic review study that is organized as follows: initially, the text brings a parameter between what education has been and what has become today due to the closure of educational institutions within the context of a pandemic, showing the primary differences in the way of teaching and learning. It also shows how exclusionary and demotivating the lack of access to new technologies is for students in public basic education, outside the classroom, in an environment that exasperates distractions. It is also observed how the faculty has worked to face the difficulties, as well as possible solutions to the connectivity problems arising from the poor distribution of income. For the purposes of this study, scientific articles by renowned authors, published in recognized journals in Brazil and in the world, were used, in addition to using our own experience within the context of the pandemic, at work, at home and in studies to endorse the project. One of the conclusions of the research indicates how distant the reality is from the desire to have accessibility for all for an equal qualification, which can guarantee a legal dispute in the world of work. It also shows that due to the lack of knowledge, countless semi-literate workers are unable to access their rights, nor help their children with schoolwork online.